Teachers in the Private and Public Spheres: Ethical Orientations in Educational Interactions - Michvocíková, Veronika; Sirotová, Mariana; Rubacha, Krzysztof; Książek, Ewelina (Journal of Education Culture and Society, 2023)
Aim. The main aim of the article is a presentation of a comparative study of differences in ethical orientations used by teachers in educational practice in two settings: in private life as parents and in the public sphere, working as teachers.Methods. First, a hypothesis was proposed to test the observations by Lawrence Kohlberg (1984) and Carol Gilligan (1993) regarding the relative stability of ethical orientations in terms of the ethics of care and justice. To this end, an assumption was made that teachers prefer the former in contacts with their own children (private sphere) while favouring the latter in relationships with students (public sphere). The paired samples t-test confirmed this hypothesis.Results. Based on the analysis, gender was found not to influence teachers’ ethical orientations in the private sphere; however, it seems to play a part in the public sphere. This ambivalence was revealed in male teachers. Contrary to gender stereotype, in contacts with their own children, they tend to lean towards the ”feminine” ethics of care, but when acting in their public capacity they perpetuate the ‘masculine’ stereotype by following the ethics of justice in their school interactions.Conclusion. It is worth emphasising the ambiguity of the results obtained and the instability of their interpretations. The actions of the teachers studied do not confirm the thesis about the stability of ethical orientations in educational work and are, therefore, indicative of ambivalence towards the role of gender in this process.